Design and thermodynamic analysis of a solar powered greenhouse for arid climates - Farhat Mahmood (15468854) (2021)
Considering the drive to develop innovative and sustainable food production systems, this study analyzes a novel renewable energy powered self-sustainable greenhouse. The system is designed based on the principles of decentralization within food production systems and sustainability to improve the food security of a region. The greenhouse unit utilizes the humidification-dehumidification phenomena using saline groundwater to provide optimum growing conditions to the plants throughout the year thus making self-sustaining agriculture possible in arid climates. The subsystems integrated in the proposed system include a greenhouse unit, parabolic trough collector, organic Rankine cycle, absorption cooling system, and thermal energy storage. A detailed thermodynamic model is developed using the mass, energy, entropy, and exergy balance equations for all the components of the system. A comprehensive parametric study is performed to determine the performance and relationship between different inputs on the outputs of the system. Results illustrate that the proposed system is capable of providing year-round essential requirements for the sustainable greenhouse in an efficient and environmentally friendly manner. The outputs of the system include 17.5–27.3 m3/day produced freshwater, 4.3 MW cooling, 1.03 MW electricity and gained output ratio of about 2.10–3.3 while maintaining optimum temperature and humidity level inside the greenhouse. Other Information Published in: Desalination License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.desal.2020.114769